2016
DOI: 10.12816/0028461
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Private Investment in Jordan : An ARDL Bounds Testing Approach = محددات الاستثمار الخاص في الأردن : باستخدام نموذج ARDL لتحليل السلاسل الزمنية

Abstract: This study investigates the determinants of private investment in Jordan for the period 1976-2012. The ARDL (Autoregressive Distributed Lag) approach to cointegration is employed to test the existence of a long run relationship, as well as to study the short run dynamics of private investment in Jordan. To that end, demand for private investment is estimated as a function of real Gross Domestic Product (real GDP), real interest rate, and real public investment. The original problem focuses on the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Studies that have used time series data include Ribeiro and Teixeira (2001), Karagöz (2010), Michael and Aikaeli (2014), Magableh andAjlouni (2016), andAwad et al (2021), among others. Ribeiro and Teixeira (2001) investigated the determinants of private investment in Brazil from 1956 to 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have used time series data include Ribeiro and Teixeira (2001), Karagöz (2010), Michael and Aikaeli (2014), Magableh andAjlouni (2016), andAwad et al (2021), among others. Ribeiro and Teixeira (2001) investigated the determinants of private investment in Brazil from 1956 to 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Using the error correction model, Michael and Aikaeli (2014) found that the variables that influence private investment growth are public investment, GDP growth, and credit to the private sector in Tanzania. In Jordan, Magableh and Ajlouni (2016), using the ARDL approach, found that private investment is positively correlated to real GDP growth and is negatively associated with real interest rates and real public investment in both the long and short run. Also, Using the ARDL approach, Gondim et al (2018) examined the relationship between outward foreign direct investment and domestic investment in Brazil and China from 1975 to 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Jordan is keen to promote domestic and foreign investments to enhance economic growth (Arabyat, 2016). The importance to promote investment in Jordan is evident from the increased attention from the government (Magableh & Ajlouni, 2016). Jordan's government focuses on the factors that influence investment promotion.…”
Section: Introductionmentioning
confidence: 99%